Smart Packaging of Temperature and Light Susceptible Product with Purple Sweet Potato (Ipomoea batatas L.) Indicator Label - Desita Wirda Ramadhan; Andrew Setiawan Rusdianto (LPPM Universitas Duta Bangsa Surakarta, 2021)
The main role of packaging in the food industry is to preserve and protect products from external contamination such as light, heat, oxygen, moisture, microorganisms, and others. Product shelf life can be increased by reducing the risk of contamination from microbes, especially for products that are vulnerable to temperature and light such as pasteurized milk. Consumers generally evaluate the quality and freshness of packaged foods through the shelf life printed on the package. Still, for some products, the shelf life date is not enough to evaluate the quality and freshness of the food. In this regard, using the color indicator packaging has been found to be an innovative and smart process for detecting, tracking and protecting the quality of food, and it turns out to be an ultimate tool for safe and convenient food packaging. Smart packaging can show the color change of the packaging film according to the state of the food and evaluate the quality or freshness of the packaged food in real-time, is increasing. Anthocyanins, a family of polyphenol-based flavonoids, are natural colorants that reflect light from red to blue in the visible spectrum. Recently, studies on anthocyanins are rapidly increasing as an alternative to toxic synthetic food colorants due to their excellent functional properties. Anthocyanin’s pH dependent color change properties are very important in that it can monitor food quality, indicate the shelf life of food, increase consumer interest in food, and eventually be used as a color indicator in food packaging applications. The pH indicator used in this study was sourced from purple sweet potato extract with edible film membranes from chitosan, and CMC. In this study, the extraction of purple sweet potatoes was carried out with ethanol: acetic acid: aquadest as a solvent with a ratio of 25:1:5 ml, so that a total anthocyanin content was obtained of 70.16 ± 0.899 mg / 100 g with a pH of 5.60 ± 0.015. The freshness parameter of the milk can be seen from the color change on the label that shows the pH of the product. If the pH gets lower than the pH of the milk, the product has spoiled. The label contains three color parameters that indicate that the milk is fresh, still fresh, and not fresh. Therefore, the pH indicator label developed can be used as a diagnostic tool to detect product freshness.